Cardamonin from Alpinia rafflesiana Wall. ex Baker as inhibitor of inflammatory responses in IFN-Gamma/LPS-Stimulated microglial cell line (BV2) via NF-κB signalling pathway - Chow, Yuh Lit (2012)
The prevalence of neurodegenerative diseases affecting the worldwide population is showing an elevating trend over the last two decades. Chronic neuroinflammation has been proven to contribute to the pathogenesis of these diseases and over-activated microglial cells as well as the inflammatory mediators produced play a crucial role in sustaining the progression of neuroinflammation. In the anti-inflammatory approach, non-steroidal anti-inflammatory drugs (NSAIDs) are among the therapeutic choices and are anticipated to be useful drugs in treating neuroinflammation. Unfortunately, NSAIDs-associated adverse effects had hampered the long term usage of these drugs and thus prompted the investigations for discovering innovative therapeutics for neurodegenerative diseases. Previously, cardamonin isolated from Alpinia rafflesiana was shown to possess promising anti-inflammatory property in macrophages and hence potential to be used as a therapeutic agent for various inflammatory diseases. However, the mechanism of action and molecular basis of cardamonin on microglial cells, which are the central nervous system (CNS)-specific macrophages, still remains unknown. Hence, the main objectives of this study were to investigate the effects of cardamonin on microglial inflammatory responses as well as its mechanism of action in cellular model of neuroinflammation.